2002
DOI: 10.1161/01.hyp.0000029240.44253.5e
|View full text |Cite
|
Sign up to set email alerts
|

P450-Dependent Arachidonic Acid Metabolism and Angiotensin II–Induced Renal Damage

Abstract: Abstract-Transgenic rats overexpressing both human renin and angiotensinogen genes (dTGR) develop hypertension, inflammation, and renal failure. We tested the hypothesis that these pathological features are associated with changes in renal P450-dependent arachidonic acid (AA) metabolism. Samples were prepared from 5-and 7-week-old dTGR and from normotensive Sprague-Dawley (SD) rats, ie, before and after the dTGR developed severe hypertension and albuminuria. At both stages, dTGR showed significantly lower rena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 41 publications
2
42
0
Order By: Relevance
“…20,21 In addition, kidney-specific downregulation of P450 epoxygenase enzymes is associated with hypertension and endorgan damage in transgenic rats overexpressing both human renin and angiotensinogen genes (dTGR). 26 We have previously reported that chronic angiotensin II infusion combined with a high salt diet was associated with decreased CYP2C11, CYP2C23, and CYP2J protein levels in renal vasculature and that this may contribute to the development of salt-sensitive hypertension. 21 The current study extends these findings by examining whether angiotensin II infusion leads to persistent salt-sensitive hypertension even after removal of the angiotensin.…”
Section: Discussionmentioning
confidence: 95%
“…20,21 In addition, kidney-specific downregulation of P450 epoxygenase enzymes is associated with hypertension and endorgan damage in transgenic rats overexpressing both human renin and angiotensinogen genes (dTGR). 26 We have previously reported that chronic angiotensin II infusion combined with a high salt diet was associated with decreased CYP2C11, CYP2C23, and CYP2J protein levels in renal vasculature and that this may contribute to the development of salt-sensitive hypertension. 21 The current study extends these findings by examining whether angiotensin II infusion leads to persistent salt-sensitive hypertension even after removal of the angiotensin.…”
Section: Discussionmentioning
confidence: 95%
“…Lyon hypertensive rats also have a decreased renal epoxygenase activity that contributes to the increase in arterial blood pressure (65,69). Transgenic rats overexpressing both human renin and angiotensinogen genes (dTGR) develop hypertension and renal failure that are associated with decreased kidney epoxygenase enzymatic activity and CYP2C11, CYP2C23, and CYP2J protein levels (53,74,75). Similarly, we have found that an inability to increase renal cortical and vascular CYP2C11 and CYP2C23 protein expression may contribute to salt sensitivity of angiotensin-dependent hypertension (109,110).…”
Section: Renal and Cardiovascular Protective Actions Of Eets And Sehmentioning
confidence: 92%
“…51 However, there are also reports linking salt-induced and angiotensin II-induced hypertension to the failure to increase epoxygenase expression, particularly in the kidney. [52][53][54] Genetic hypertension seems to be differentially linked to CYP expression and activity, because there seems to be no difference in the arachidonic acid-induced generation of EETs by kidneys from SHRs and Wistar-Kyoto rats. 51 Such data imply that alternative mechanisms may underlie the increased renal vasodilator effect of arachidonic acid in the SHR kidney.…”
Section: Eets and Hypertensionmentioning
confidence: 99%